2016
DOI: 10.24135/teacherswork.v13i1.95
|View full text |Cite
|
Sign up to set email alerts
|

Secondary student teachers' personal values and perceptions of Teaching as Inquiry

Abstract: Teaching as Inquiry is a framework in the New Zealand Curriculum for guiding teachers' professional decision-making and actions (Ministry of Education, 2007) THEORETICAL FRAMEWORKThe theoretical framework for this article assumes Teaching as Inquiry to be: a cyclical process in which questions are posed, evidence is gathered, and decisions are made. The primary purpose of teaching as inquiry is to improve outcomes for students through purposeful assessment, planned action, strategic teaching and focused revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Furthermore, teachers' perspectives on diversity should be examined two-dimensionally, from the personal and professional perspective. Research in the domain of teachers' professional identity shows that the development of teachers' identity is influenced by both their personal and professional beliefs and values (Vermunt, 2016;Vizek Vidović & Domović, 2019), which is why Pohan and Aguilar (2001) argue that teachers' professional and personal beliefs about the same diversity phenomenon need not always complement each other. This argument is confirmed by research on the personal and professional beliefs of teachers on diversity conducted by Cardona (2005) in the Alicante province in Spain, which showed that the participants had more positive professional than personal beliefs.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, teachers' perspectives on diversity should be examined two-dimensionally, from the personal and professional perspective. Research in the domain of teachers' professional identity shows that the development of teachers' identity is influenced by both their personal and professional beliefs and values (Vermunt, 2016;Vizek Vidović & Domović, 2019), which is why Pohan and Aguilar (2001) argue that teachers' professional and personal beliefs about the same diversity phenomenon need not always complement each other. This argument is confirmed by research on the personal and professional beliefs of teachers on diversity conducted by Cardona (2005) in the Alicante province in Spain, which showed that the participants had more positive professional than personal beliefs.…”
Section: Introductionmentioning
confidence: 99%